Novel indazole Schiff base metal chelates as potential antifungal agents: synthesis, characterization, and computational analysis - Kamal El-Baradie; Yusif S. El-Sayed; Nadia El-Wakiel; Basma M. Salem; Asmaa El-Nagar (Chemical and Biological Technologies in Agriculture)
Abstract Soil-borne phytopathogenic fungi pose a significant risk to many economically important crops due to their ability to survive in the soil for extended periods without a host. Thus, a novel Schiff base (HL), 3-(1H-indazol-5-ylimino)-1-phenylbut-1-en-1-ol, was synthesized by the condensation of 5-aminoindazole with benzoyl acetone. Its Co2+, Ni2+, and Cu2+ chelates were also synthesized. These compounds were characterized by FT-IR, 1H-NMR, 13C-NMR, UV–Vis, EI–mass spectroscopy, XRD, TGA, magnetic susceptibility, elemental analysis, and molar conductance. The ligand possesses an enol form and functions as a monobasic bidentate through the deprotonated OH and C=N groups. The Co2+ and Ni2+ ions produced 1:1 (M:L) chelates, whereas Cu2+ ion produced a 1:2 (M:L) chelate. From the characterization results and the DFT method, it was revealed that the Co2+ chelate has tetrahedral geometry, while Ni2+ and Cu2+ chelates are octahedral. The antifungal activities of the ligand and the metal chelates were evaluated against some plant pathogenic fungi, namely, Stromatinia cepivora, Botrytis allii, Rhizoctonia solani, and Sclerotinia sclerotiorum in comparison with the commercial fungicide Tebuconazole. The Ni+2 chelate emerged as the most potent agent that achieved 100% inhibition for the S. cepivora and S. sclerotiorum. It also caused significant morphological alterations in S. sclerotiorum as revealed by the SEM micrograph. The treated S. sclerotiorum hyphae displayed irregular, shriveled, and collapsed structures in contrast to the smooth and robust appearance of the control. The molecular docking study further confirmed that Ni2+ chelate strongly interacted with the active site of CYP51 protein compared with Co2+ and Cu2+ chelates and the fungicide Tebuconazole. The superior efficacy of Ni2+ chelate offers a promising alternative to traditional fungicides. Graphical Abstract